Bank Regulation and Supervision around the World : A Crisis Update - Čihák, Martin (World Bank, Washington, DC, 2013)
This paper presents the latest update of the World Bank Bank Regulation and Supervision Survey, and explores two questions. First, were there significant differences in regulation and supervision between crisis and non-crisis countries? Second, what aspects of regulation and supervision changed significantly during the crisis period? The paper finds significant differences between crisis and non-crisis countries in several aspects of regulation and supervision. In particular, crisis countries (a) had less stringent definitions of capital and lower actual capital ratios, (b) faced fewer restrictions on non-bank activities, (c) were less strict in the regulatory treatment of bad loans and loan losses, and (d) had weaker incentives for the private sector to monitor banks' risks. Survey results also suggest that the overall regulatory response to the crisis has been slow, and there is room to improve regulation and supervision, as well as private incentives to monitor risk-taking. Specifically, comparing regulatory and supervisory practices before and after the global crisis, the paper finds relatively few changes: capital ratios increased (primarily among non-crisis countries), deposit insurance schemes became more generous, and some reforms were introduced in the area of bank governance and bank resolution.